Advanced Methods and Technologies for Agent and Multi-Agent Systems. - Edited by (IOS Press, 2013)
The field of agent and multi-agent systems is concerned with the development and evaluation of sophisticated, AI-based, problem solving and control architectures for both single and multi-agent systems. This book presents the proceedings of the 7th KES Conference on Agent and Multi-agent Systems - Technologies and Applications (KES-AMSTA 2013), held in Hue City, Vietnam, in May 2013. The KES-AMSTA 2013 conference provides an internationally respected forum for scientific research in the technologies and applications of agent and multi-agent systems. In all, 44 papers were selected for oral pres.